Analysis of color vision and cognitive function in first-episode schizophrenia before and after antipsychotic treatment. (August 2022) - Duan, Li; Tian, Chunsheng; Fu, Chunfeng; He, Juan; Dai, Jiali; Shao, Xiaojun; Zhu, Gang
Abstract: Background: A large body of recent research has demonstrated that patients with schizophrenia exhibit significant changes in visual function and ocular tissue structure in the early stages of onset. It is therefore possible to explore a novel scientific breakthrough in the etiology of schizophrenia by transforming the traditional study of brain structure and function with a view to examining the potential field of eye tissue and function. However, few studies have investigated the correlation between iris characteristics and schizophrenia, and evidence is lacking in this regard. Thus, further exploration is needed. Purpose: This study was designed to analyze the characteristics of iris structure, color vision function and cognitive function, as well as the changes therein in patients with the first-episode drug-free schizophrenia before and after antipsychotic treatment. It aimed to preliminarily identify easily-measurable biomarkers for early clinical screening and diagnosis of schizophrenia. Methods: This study recruited 61 patients (22 males) with first-episode schizophrenia. Prior to the commencement of treatment with antipsychotic drugs, the Montreal Cognitive Assessment (MoCA) and Farnsworth-Munsell Dichotomous (D-15 Hue Test) were used as assessment tools to evaluate cognitive function and color vision function, respectively. Over a 6-week period, patients received a second-generation antipsychotic treatment (all converted to olanzapine equivalent dose) as prescribed by the doctor, and the Positive and Negative Syndrome Scale (PANSS) was applied to evaluate the clinical treatment effects before treatment (baseline), as well as at the 2nd, 4th, and 6th weeks after drug treatment. On the basis of iris characteristics, the patients were divided into groups. The observed differences in drug treatment effects between the groups were then compared and analyzed to further clarify the relationship between treatment efficacy and iris characteristics. Finally, changes in the cognitive function and color vision function of patients at baseline and at the 6th week after drug treatment were compared, and the effects of antipsychotic drug treatment on the above-mentioned functions were analyzed. Results: On the basis of structural iris characteristics, 61 patients were classified as follows: 28 patients without iris crypts and 33 with iris crypts; 35 without iris pigment dots and 26 with iris pigment dots; 42 without iris wrinkles and 19 with iris wrinkles. No significant difference was observed in the PANSS scores of all of the patients at baseline; however, significant differences were found in patients with iris crypts and iris pigment dots at each follow-up timepoint (i.e., at the 2nd, 4th, and 6th week). Moreover, it is noteworthy that, compared with other patients, the PANSS scores of patients without specific iris structure characteristics (iris crypts and pigment dots) decreased significantly ( P< 0.05), which indicated that the drug therapy was highly effective. Excluding the interference of drug factors, a significant correlation was found between the results of the D-15 (color vision function) and MoCA (cognitive function) in first-episode untreated patients ( r = −0.401, P < 0.05). In addition, the MoCA scores (mean difference = 2.36, t = 10.05, P ˂ 0.01) were significantly higher after 6 weeks of antipsychotic drug treatment compared to conditions at baseline. Conclusions: The findings of this study demonstrated that color vision function of patients with schizophrenia improved with the improvement of cognitive function. The structural characteristics of the iris with crypts and pigment dots could have a significant impact on the drug treatment effect of schizophrenia and could be considered as a potential biomarker for detecting and recognizing schizophrenia.